1995
DOI: 10.4049/jimmunol.155.11.5449
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mapping of a pathogenically relevant BP180 epitope associated with experimentally induced murine bullous pemphigoid.

Abstract: Bullous pemphigoid (BP) and herpes gestationis (HG) are subepidermal blistering diseases associated with an autoimmune response directed against BP180, an epidermal hemidesmosomal glycoprotein. The pathogenic relevance of this Ag/Ab system was established by the recent demonstration that IgG Abs reactive with the murine form of BP180 (mBP180) are capable of triggering a subepidermal blistering disease after passive transfer into neonatal BALB/c mice. The aim of the present study was to determine the fine speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…A study by Liu et al has shown passive transfer of rabbit antimurine IgG antibodies against BP180 can lead to blistering disease with key immunopathological features of BP via complement activation ( 46 ). Epitope mapping studies have demonstrated that pathogenic antibodies in this animal model recognize the murine BP180 NC14A region, which has sequence overlap with regions of the immunodominant human BP180 NC16A epitopes ( 47 ). Further studies using C4-deficient, C1q-deficient, mast cell-deficient, neutrophil-depleted, and neutrophil elastase-null [NE(-/-)] mice demonstrated that the mechanisms involved include complement activation, mast cell degranulation, neutrophil infiltration, secretion of proteases, and BP180 cleavage ( 46 , 48 51 ).…”
Section: An Updated Understanding Of the Pathogenesis Of Bullous Pemp...mentioning
confidence: 97%
“…A study by Liu et al has shown passive transfer of rabbit antimurine IgG antibodies against BP180 can lead to blistering disease with key immunopathological features of BP via complement activation ( 46 ). Epitope mapping studies have demonstrated that pathogenic antibodies in this animal model recognize the murine BP180 NC14A region, which has sequence overlap with regions of the immunodominant human BP180 NC16A epitopes ( 47 ). Further studies using C4-deficient, C1q-deficient, mast cell-deficient, neutrophil-depleted, and neutrophil elastase-null [NE(-/-)] mice demonstrated that the mechanisms involved include complement activation, mast cell degranulation, neutrophil infiltration, secretion of proteases, and BP180 cleavage ( 46 , 48 51 ).…”
Section: An Updated Understanding Of the Pathogenesis Of Bullous Pemp...mentioning
confidence: 97%